Herpes simplex virus-1 triggered hemophagocytic lymphohistiocytosis in a patient with granulomatosis with polyangiitis - Vanessa A. States; Meghan E. Kapp (University of São Paulo, 2022)
Hemophagocytic lymphohistiocytosis (HLH) is a rare, aggressive hyperinflammatory syndrome in which an inciting event triggers massive, uninhibited activation of T lymphocytes and macrophages. Although viral infections are the most common trigger of HLH, cases of HSV-1 induced HLH are rare in adults. We present the case and postmortem findings of a 27-year-old woman diagnosed with HLH in the setting of immunosuppression for the treatment of granulomatosis with polyangiitis (GPA). Autopsy revealed evidence of herpes simplex virus-1 (HSV-1) infection and no findings suggestive of GPA recurrence.